Enhanced Production of Cellulase from Pineapple Waste by Response Surface Methodology - P. Saravanan; R. Muthuvelayudham; T. Viruthagiri (Journal of Engineering)
Optimization of the media components for cellulase production using Trichoderma reesei was carried out. The optimization of cellulase production using pineapple waste as substrate was performed with statistical methodology based on experimental designs. The screening of nutrients and their influence on the cellulase production was studied using a Plackett-Burman design. Avicel, soybean cake flour, KH2PO4, and yeast extract were found to have the positive influence for the production of cellulase. The selected components were optimized using response surface methodology. The optimum concentrations are avicel: 26.5 g/L, soybean cake flour: 22.5 g/L, KH2PO4: 4.5 g/L, and yeast extract: 12.3 g/L. A maximum cellulase activity of 8.61 IU/mL was obtained under the optimized medium in the validation experiment.